2015
DOI: 10.1038/ncomms7915
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular MRP8/14 is a regulator of β2 integrin-dependent neutrophil slow rolling and adhesion

Abstract: Myeloid-related proteins (MRPs) 8 and 14 are cytosolic proteins secreted from myeloid cells as proinflammatory mediators. Currently, the functional role of circulating extracellular MRP8/14 is unclear. Our present study identifies extracellular MRP8/14 as an autocrine player in the leukocyte adhesion cascade. We show that E-selectin–PSGL-1 interaction during neutrophil rolling triggers Mrp8/14 secretion. Released MRP8/14 in turn activates a TLR4-mediated, Rap1-GTPase-dependent pathway of rapid β2 integrin acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
159
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 149 publications
(166 citation statements)
references
References 45 publications
7
159
0
Order By: Relevance
“…The S100A9-mediated pathway leading to the transendothelial migration of neutrophils has recently been elucidated at the molecular level. 32,33 The ligation of P-selectin glycoprotein-1 by E-selectin expressed on the luminal surface of inflamed endothelial cells stimulates neutrophils to secrete S100A9, which, in turn, transmits activation signals via TLR4 in an autocrine manner. The TLR4-mediated cell activation results in the upregulated expression of high-affinity b2 integrins on neutrophils that interact with ICAM-1 expressed on endothelial cells, thereby allowing circulating neutrophils to be trapped on the luminal surface of the endothelium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The S100A9-mediated pathway leading to the transendothelial migration of neutrophils has recently been elucidated at the molecular level. 32,33 The ligation of P-selectin glycoprotein-1 by E-selectin expressed on the luminal surface of inflamed endothelial cells stimulates neutrophils to secrete S100A9, which, in turn, transmits activation signals via TLR4 in an autocrine manner. The TLR4-mediated cell activation results in the upregulated expression of high-affinity b2 integrins on neutrophils that interact with ICAM-1 expressed on endothelial cells, thereby allowing circulating neutrophils to be trapped on the luminal surface of the endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of this S100A9-dependent crosstalk between neutrophils and endothelial cells, neutrophils swiftly extravasate and accumulate in inflammation foci. 32 Therefore, impaired neutrophil recruitment to the site of granuloma formation in tasquinimod-treated animals may be attributed, at least in part, to the specific blockade of the S100A9 autocrine loop.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, MRP8/14 has been shown to promote neutrophil adhesion and, possibly, other neutrophil functions [60,61]. A recent report also revealed that MRP8/14 is released upon neutrophil rolling on E-selectin-coated endothelial surfaces and then promotes rapid activation of β 2 integrin-mediated neutrophil adhesion by binding to the TLR4 receptor [62], contributing to the amplification of neutrophil recruitment. …”
Section: Other Paracrine Amplification Mechanismsmentioning
confidence: 99%
“…The proinflammatory activity of S100A8/A9 includes recruitment of leukocytes, promotion of cytokine and chemokine secretion, and regulation of leukocyte adhesion and migration. Similar to alarmins and danger-associated molecular pattern (DAMP) molecules, S100A8/A9 activates cellular nuclear factor-kappa B (NF-kB) and mitogen-activated protein kinase (MAPK) pathways, leading to amplification of the proinflammatory cascade through the binding and activation of PRRs, such as receptors for advanced glycation end products (RAGE) and TLR-4 [8][9][10][11][12][13][14][15][16][17] . A Table 2.…”
Section: Biological Function Of S100a8/a9mentioning
confidence: 99%
“…EIU models and AAU patients Elevated S100A8 promotes the migration and infiltration of inflammatory cells in EIU; serum levels of S100A8 are elevated and synchronized with AAU progression Wang YQ et al(2016) recent study has shown that extracellular S100A8 and S100A9 also regulate β2 integrin-dependent neutrophil slow rolling and adhesion [17] .…”
Section: Biological Function Of S100a8/a9mentioning
confidence: 99%